Therapeutic effect of Al-Quran murattal (surah yusuf) on blood pressure level in pregnant women with preeclampsia - Rejeki, Sri; Trimuliani, Sumastia; Machmudah, Machmudah; Khayati, Nikmatul (South East Asia Nursing Research, 2020)
Pre-Eclampsia was recorded as a cause of maternal death in Indonesia in 2017, which was 28.8%. Hypertension is a sign of pre-eclampsia. Murattal Therapy Letter Yusuf is a non-pharmacological therapy that can be used to reduce blood pressure. The purpose of this study is to determine the effect of Murattal Therapy in reducing blood pressure in pregnant women with pre-eclampsia. The design of this study used the Quasy Experiment design with One Group Pretest and Posttest Design. As the population are pregnant women who are diagnosed with pre-eclampsia. 15 respondents were selected using purposive sampling. Data collection tool with an observation sheet and tensimeter. The data collection technique was carried out using the respondent placed in a conditioned room, then listening to the letter of Joseph for 15 minutes using a tape recorder and then his blood pressure was measured. From the 15 respondents after Murotal therapy, the result of a decrease in blood pressure with a statistical test using a paired t-test obtained a p-value of systolic blood pressure of 0,000 and diastolic blood pressure of 0,000. Murattal therapy can stimulate a controlled autonomic nerve and cause secretion of epinephrine and norepinephrine by the controlled adrenal medulla. Control hormones epinephrine and norepinephrine will inhibit the formation of angiotensin which can reduce blood pressure. Surah Yusuf's Murattal Therapy can reduce the blood pressure of pregnant women with pre-eclampsia.